A meta-analysis of the influence of traditional Chinese exercises on cognitive function in the elderly - Liu, Xueqi; Sun, Dewei; Zhao, Weiran; Zhang, Xiaoying; Wu, Yixin (Frontiers in Psychology, 2025)
BackgroundThis study seeks to assess the impact of traditional Chinese exercises (Tai Chi, Baduanjin, Yijinjing, Wuqinxi, and Liuzijue) on cognitive function in older adults through a systematic review and meta-analysis. It examines their effects on global cognitive performance, as well as specific cognitive domains, providing robust evidence to support the enhancement of cognitive function in the elderly.MethodsA thorough search was executed across eight key databases, including PubMed, Embase, Cochrane Library, EBSCO, Web of Science, Wanfang Data, the Chinese Science and Technology Journal Database, and China National Knowledge Infrastructure. The quality of the studies that met the inclusion criteria was assessed using the Cochrane Collaboration tool for evaluating risk of bias. Data synthesis was performed using Review Manager 5.4, where pooled intervention outcomes were expressed as mean differences (MD) alongside their 95% confidence intervals (CI). Additional sub-group analysis was conducted to explore potential factors contributing to heterogeneity.ResultsThis systematic review and meta-analysis evaluated data from 29 randomized controlled trials, encompassing a total of 2,489 participants. The results demonstrate that traditional Chinese exercises substantially improve language abilities (Category Verbal Fluency: MD = 0.90, 95% CI: 0.38 to 1.41), executive function (TMT B: MD = −13.70, 95% CI: −16.06 to −11.35), short-term memory (MD = 0.85, 95% CI: 0.42 to 1.29), and long-term delayed recall (MD = 1.39, 95% CI: 0.72 to 2.06). Sub-group analysis indicated that baseline cognitive function plays a critical role in determining the effectiveness of the intervention. Patients with cognitive impairment derive significantly greater benefits from traditional Chinese exercise interventions than those with normal cognitive function.ConclusionThis study found that the traditional Chinese exercises can enhance cognitive function in the elderly, particularly in those with mild cognitive impairment. The effects of traditional Chinese exercises differed across various cognitive domains, indicating that when utilizing traditional Chinese exercise as an intervention, it is crucial to consider the specific cognitive status of the patient to design precisely tailored intervention strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42024535287, identifier [CRD42024535287].